A Comparative Study of The Students’ Critical Reading Competency on High Order Thinking Items in A Junior High School - Rini, N.K. Ratna Kusuma; N.L.P, D.K. Tantra,; Dewi, Eka Sulistia (LPPM Undiksha, 2020)
This study aims to analyze and describe the students’ reading competencies and comparing simultaneously the students reading competencies on high order thinking items across classes, text genres, and reading indicators. The design implemented was descriptive in order to answer the first research question and comparative research in order to answer the second research questions. The instrument used for data collection was reading competency test. The data were then analyzed descriptively and inferentially by implementing a parametric statistic, namely: central tendency measures; measures of dispersion; and simultaneous comparison. The present study was applied one-way ANOVA as the inferential analysis. The result showed, the significant value of one-way ANOVA on the students Reading Competency was 0.75. The significant figure was higher than 0.05. As a result, the students reading competency in high order thinking items was not significant. Therefore, the null hypothesis was accepted. It can be drawn a conclusion that the students reading competencies on high-order-thinking items across classes, text genres, and reading indicators are in below average.